Edukasi Dan Implementasi Relaksasi Guided Imagery Untuk Mengurangi Nyeri Pada Pasien Dewasa Post Operasi - Viola Santesa; Septian Mixrova Sebayang; Arlyana Hikmanti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Postoperative pain is a common complication experienced by patients and is generally managed using pharmacological analgesics, which may cause side effects. Therefore, nonpharmacological approaches such as guided imagery are needed as complementary interventions in pain management. Objective: The purpose of this service was to increase knowledge and reduce pain levels among adult postoperative patients through education and implementation of guided imagery at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. Method: This public service was conducted with 30 adult postoperative patients experiencing mild to moderate pain. The activity included health education using leaflets and the implementation of guided imagery through a 15-minute audio recording. Knowledge levels were assessed using pre-test and post-test questionnaires, whereas pain intensity was measured with the Numeric Rating Scale (NRS). Result: The study showed that patient knowledge increased, with the proportion in the poor category declining from 93.3% and the majority reaching the good category (83.3%). Pain intensity also decreased from moderate pain (70%) to mild pain (76.7%) post-intervention. Conclusion: Guided imagery education and implementation were effective in improving patient knowledge and reducing postoperative pain, supporting its potential use as a nonpharmacological intervention in hospital-based pain management services.